2015
DOI: 10.4236/fns.2015.69085
|View full text |Cite
|
Sign up to set email alerts
|

Does Argan Oil Supplementation Affect Metabolic Parameters and Behavior in Wistar Rats?

Abstract: Argan oil is renowned for its particular biochemical profile: high-fat oleic and linoleic acids, tocopherols, sterols, polyphenols. This composition gives it nutritional, therapeutic and preventive properties against dermatological, metabolic and proliferative diseases. The composition of argan oil assigns its benefits to mental health; it would be provided with possible effects on the prevention and/or cure of stress related disorder. This work aims to evaluate the impact of argan oil dietary on the behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Notably, we demonstrated that UCMS-induced behavior changes could be reversed by prolonged administration of AO (10 mg/kg/day), which confirmed further the antidepressant effect of AO. These data are in line with a previous study conducted in our laboratory, evaluating the impact of AO dietary on the behavioral response to stress, using depressive and anxiety measurement paradigms [15]. Without using a stress induction procedure, the results of the study referred to, showed that AO supplementation (10 ml/Kg/day) during 13 weeks has resulted in an increase in locomotor activity and reduced sensitivity to frightening environments (FST, EPM and OFT).…”
Section: Antidepressant-like Effects Of Ao Supplementationsupporting
confidence: 90%
See 3 more Smart Citations
“…Notably, we demonstrated that UCMS-induced behavior changes could be reversed by prolonged administration of AO (10 mg/kg/day), which confirmed further the antidepressant effect of AO. These data are in line with a previous study conducted in our laboratory, evaluating the impact of AO dietary on the behavioral response to stress, using depressive and anxiety measurement paradigms [15]. Without using a stress induction procedure, the results of the study referred to, showed that AO supplementation (10 ml/Kg/day) during 13 weeks has resulted in an increase in locomotor activity and reduced sensitivity to frightening environments (FST, EPM and OFT).…”
Section: Antidepressant-like Effects Of Ao Supplementationsupporting
confidence: 90%
“…Rats were aged 21 days (at weaning) when AO supplementation began. They were supplemented daily by intra-gastric gavage (1 ml of AO/100 g of body weight, between 8:00 am and 10:00 am) [13][14][15]42,43] during 10 weeks (i.e., from 21th to 93th PND). Control animals were treated orally for the same duration with NaCl 0.9%.…”
Section: Ao: Oral Gavage Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, our laboratory (GNBL) demonstrated, by using animal models, that certain alternative treatments complementary to conventional pharmacology had possible beneficial effects against emotional and cognitive disorders. It is mainly a pretreatment with Argan oil (AO) [21,22], obtained from the seeds of Argania spinosa L., tree endemic to Morocco. This oil has been widely used in traditional medicine as a natural remedy for several centuries [23].…”
Section: Introductionmentioning
confidence: 99%